Carcass Characteristic from Different Sex of Horse Fed with Local Forage in Jeneponto Regency, South Sulawesi - Ayu Lestari (Jurnal Biologi Tropis, 2022)
Horses are livestock which are used as a source of meat for the people in Jeneponto Regency. Horse rearing is still traditional where horses are kept in a semi-intensive system and consume local forages. Slaughtering of horses in this area was carried out at slaughterhouses that produce carcasses as a product. Horses slaughtered, both stallions and mares, range in age from 3-7 years. Based on this background, it is necessary to conduct research because it is not yet known how horse carcasses are produced from this feeding system when viewed from sex differences. The research was carried out from August to September 2022 at slaughterhouses spread across the Jeneponto Regency, South Sulawesi. The types of horses slaughtered and examined for their carcasses were Sumba horses, Sulawesi/Bugis horses. Carcass weight data were tested using one-way ANOVA and H-test in SPSS 2020. The results showed that male carcass weight was higher than female carcass weight. The male horse carcass weight was 120.20 ± 6.38 kilograms, while the female body weight was 107.4 ± 6.19 kilograms. The correlation between sex and carcass weight in horses fed local feed showed a significant relationship (p<0.05). Based on the results of the study, it can be concluded that there is a significant difference in carcass weight between stallions and mares by feeding local forages and there was a correlation between the sex of horses fed with local forage and the weight of the carcass produced.